ILLOCUTIONARY ACT ON ALEX’S DIALOGUE IN MOVIE MADAGASCAR 3: EUROPE’S MOST WANTED - Fransisca Fransisca; Sortha Silitonga (State University of Medan, 2013)
ABSTRACT This research deals with the analysis of illocutionary act on Alex’s dialogue in movie Madagascar 3: Europe’s Most Wanted. The objectives of the study are to find types of illocutionary act, the most dominant type, and the reason why the most dominant type occurs. The research on this thesis was carried out on descriptive qualitative design. The sources of data were derived from the script of Alex’s dialogue. The data were analyzed based on Yule’s theory and they were classified into five types namely; representative, directive, commissive, expressive and declarative. The most dominant type of illocutionary act used there is representative. The total percentage is: representative 42.90%, directive 38.26%, commissive 3.19%, expressive 12.75%, and declarative 2.90%. Representative becomes the most dominant type because there are many elements of representative used such as arguing, asserting, denying, informing and describing. Keywords: Pragmatics, Speech Act, Illocutionary Act, Madagascar 3: Europe’s Most Wanted.